Thermal activation of stress-induced martensitic transformation in Ni-rich Ti-Ni alloys. (September 2020) - Niitsu, K.; Date, H.; Kainuma, R.
Abstract: We performed compression tests at low temperatures under various strain rates for Ni-rich Ti-Ni alloys. Thermal activation theory for the habit plane motion with a thermal activation energy of ~0.5 eV successfully reproduced both the examined temperature and strain-rate dependences of the transformation stress hysteresis. This indicates that the thermal activation process of the habit plane motion underlies the dramatic increase in the transformation hysteresis at lower temperatures in this system. These findings are critical to elucidate the physical impact of the thermal activation nature on the transformation hysteresis and to consider the feasibility of low-temperature operation of shape-memory functions. Graphical abstract: Image, graphical abstract